The Bioproductive Effect of Broiler Lighting Program - Monica Parvu; Ioana Cristina Andronie; Violeta Elena Simion; Adriana Amfim (Scientific Papers Animal Science and Biotechnologies, 2023)
The aim of the study was to evaluate the productive performances of the ROSS 308 broiler exposed to the alternative lighting program, starting from the third week: the control group C with nearly continuous program (23L:1D), the experimental group E1 with intermittent program of 16 h light (2L:1D) and the experimental group E2 with combined program of 16 h light (6L and six period 2L:1D). Three groups of 35000 chickens – one day old were experimented on. The chickens were raised in intensive system. The experimental period was 35 days. Compared with the control group, at the experimental groups the daily gain was less up to 4.6%, but the differences were not significant; the feed intake was significantly less up to 7% (p≤0.05), as a consequence of reducing the time of feeding. The viability was 95.8% at E1, 96.6% at E2 and 93.2% at the control group, the differences being insignificant. At the experimental group E2, the incidence of leg problems was significantly less.  By applying the combined lighting program, the chickens have manifested the natural behaviour of feeding, resting and physical activity; they have allowed a higher capitalization of the nutrients and have ensured a better uniformity.